The Effect of Work Stress and Compensation on Turnover Intention Mediated by Organizational Commitment to Employees of PT Wahana Semesta Banten - Bayu Pramono, Bayu Pramono; Mariati Tamba, Mariati Tamba; Ani Nuraini, Ani Nuraini (LPPM Universitas Respati Indonesia, 2023)
This study aims to prove the effect of work stress and compensation on turnover intention mediated by organizational commitment. The high turnover rate during the COVID-19 pandemic made researchers interested in conducting research at PT Wahana Semesta Banten (Radar Banten), Serang City. The sample of this study amounted to 53 employees, with the sampling technique using quota sampling. The data analysis technique in this study uses Structural Equational Modeling (SEM) with the path analysis method using the SmartPLS application. The results showed that job stress had an effect on turnover intention. Job stress has no effect on organizational commitment. Job stress has no effect on turnover intention through organizational commitment. Compensation has no effect on turnover intention. Compensation affects organizational commitment. Compensation has no effect on turnover intention through organizational commitment. In conclusion, work stress causes turnover intention in Radar Banten. Organizational commitment also cannot mediate work stress and compensation on turnover intention. Good organizational commitment will avoid turnover intention. Therefore, companies need to create work programs that can reduce work stress levels and maintain employee organizational commitment. Keywords : Job Stress, Compensation, Organizational Commitment, Turnover